A nod to paratuberculosis: NOD1 and NOD2 expression in the pathological spectrum of Mycobacterium avium subsp. paratuberculosis infection in cattle - Zapico, David; Espinosa, José; Mendívil, Pedro; Criado, Miguel; Benavides, Julio; Fernández, Miguel (Frontiers in Veterinary Science, 2025)
Mycobacterium avium subsp. paratuberculosis causes various types of granulomatous lesions in cattle, ranging from focal lesions associated with latency to diffuse lesions observed in animals with clinical disease. While the exact determining factors are unknown, recent evidence highlights the key role of innate immunity in the outcome of the infection. NOD-like receptors, which are innate immune proteins, play a significant role in recognizing intracellular pathogens, including mycobacteria. This study aimed to evaluate the expression of NOD1 and NOD2 in intestinal samples from cattle with different types of lesions associated with paratuberculosis: focal, diffuse paucibacillary, and multibacillary forms. The expression of NOD1 and NOD2 was assessed according to the number of immunolabeled cells, and only those cells consistent with macrophages were considered. A significant increase in the number of NOD1+ and NOD2+ macrophages was observed in cattle with diffuse multibacillary forms compared to the other groups. No expression of NOD1 or NOD2 was detected in the focal and diffuse paucibacillary lesions, while a strong expression of NOD2 and occasional NOD1 was observed in the multibacillary granulomas. These findings suggest that NOD1 and NOD2 are involved in the pathogenesis of bovine paratuberculosis.